Stigmatisation of Youth in Residential Care as Epistemic Violence - Sara Blumenthal (Social Work and Society)
The following article illustrates the stigmatisation of youth by caregivers in residential care drawing on ethnographic field notes and interview material gathered within an Austrian facility. Based on these results, the article argues that stigmatisation not only allows violence, but is in itself a form of violence, namely epistemic violence. With the concept of epistemic violence, the knowledge dimensions of violence, such as devaluating the addressees of residential care, is pointed out. Within the presented ethnographic material, epistemic violence can also be traced back to limited forms of pedagogical practice on part of the caregivers. The article concludes, that the occurrence of epistemic violence by caregivers points towards the need for reforms on three levels ï€ the training and further education of caregivers, reforms within the field of residential care and reforms of the broader spectrum of social services.